Analisis Pengaruh Reliability Sistem Informasi Institusi XYZ Terhadap Kinerja Komisi Berbasis Web - christy mahendra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
A In administrative governance, the XYZ institution still manages it manually. The accountability report is reported in print out form. In this research, XYZ institution developed a web-based information system. This study analyzes the reliability of information systems on the influence of commission performance. This study uses ISO 9001: 2008 for questionnaires and regression calculations in testing a hypothesis. The hypothesis offered is as follows, H0: There is no effect of XYZ Information System on performance and in commission governance. H1: There is an influence of the XYZ Information System on performance and on commission governance. To find out whether the hypothesis is successful or not, research needs to look at the t table value with the provisions α / 2 = 0.05 / 2 = 0.025, side test because you want to know the significant regression coefficient. If the t value <t table value, H0 is accepted. If the value of t count> the value of t table, H0 is rejected. Anova test is used as the basis for making simple linear regression test decisions by comparing the significant value with the probability value of 0.05: If the significant value is <0.05; this means that the variable x affects the variable y. Based on the value of t: it is known that the value of t count is 3.572> t table = 2.048, so it can be concluded that the variable SI (X) affects the variable Performance (Y). These results answer the hypothesis H1.